معاني "ما" في سورة المائدة : THE MEANINGS OF "MAA" IN SURAT AL-MAIDAH - Ilham Tumanggor; Abdul Wadud, Usamah; TIY Kusmarrabbi Karo (El-Jaudah : Jurnal Pendidikan Bahasa dan Sastra Arab, 2022)
The Qur'an is a revelation from Allah swt to the Prophet Muhammad and it contains so many stories of the previous prophets that can be learned and the Qur'an is also a guide to the universe and a source of knowledge. Allah swt sent down the Al-Quran in Arabic so that in order to understand and take wisdom from it it is necessary to master Arabic, There are several branches of knowledge that must be mastered in order to understand Arabic well, one of which is Nahu Science. There are many topics discussed in Nahu science and one of the discussions is about "ma". and because of the various types and meanings of "ma" the writer feels the need to research it, because if you misinterpret "ma" then you will also misunderstand what you read or hear. The formulation of the problem in this study is how many ma in Surah Al-Maidah?, and what types of ma in Surah Al-Maidah?, and what are the meanings of ma in Surah Al-Maidah?. The purpose of this study is to determine the number of ma in Surah Al-Maidah, then to find out what are the types and meanings of Ma in Surah Al-Maidah, this type of research is qualitative research, using the literature review method, for data collection using documentation method and analyze data using descriptive method. The results obtained from this study are as follows: The number of ma in Surah Al-Maidah is 112 surah, and the types are ismiyah and harfiyah. And "ma" is located in 69 verses in Surah Al-Maidah, while the meanings of ma in Surah Al-Maidah are ma al-maushulah in 78 places, ma al-nafiyah in 13 places, ma al-kafah in 7 places. , ma al-mashdariyah a number of 5 letters, ma al-istifhamiyah a number of 3 places, ma al-nafiah who does laisa a number of 3 places, ma al-zaidah a number of 2 places.